Communication Arts majors was given honorable mention at the Teruel Film and Video Festival in Spain - Barles, Gina (Animo Repository, 1989)
The video documentary, Aliwan, produced by Communication Arts majors Gina Barles, Jennifer Lim and Grace Cielo Salibay was given honorable mention at the Teruel Film and Video Festival in Spain. The 17-minute documentary on child prostitution in Pagsanjan was named Best Project by the Department in 1987. Narration of the Spanish translation was by Benjamin de la Fuente.